2022
DOI: 10.1016/j.asieco.2022.101450
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID-19 pandemic more contagious for the Asian stock markets? A comparison with the Asian financial, the US subprime and the Eurozone debt crisis

Abstract: The ongoing COVID-19 pandemic has sent shock waves across the global stock markets. Several financial crises in the past too have had a global impact with their reach extending beyond the country of origin. The current study compares the contagion effect of four such crises viz. the Asian financial crisis, the US subprime crisis, the Eurozone debt crisis, and the currently ongoing Covid-19 crisis on Asian stock markets to understand which of these has had the most severe impact. It finds that among all the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 83 publications
3
12
0
Order By: Relevance
“…For the volatility, the period with more positive spatial dependence is the sub-prime crisis, followed by the Euro debt crisis; however, for the MVaR, the sub-prime period remains the one that causes the greatest positive spatial dependence between extreme losses but is followed by Brexit. Similar results on the US subprime crisis have been obtained in recent work by Chopra and Mehta [25], these authors showed that the sub-prime crisis was the most contagious for the Asian stock markets. In addition, previous works also showed the contagion of this crisis in different financial markets around the world, see [16,17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For the volatility, the period with more positive spatial dependence is the sub-prime crisis, followed by the Euro debt crisis; however, for the MVaR, the sub-prime period remains the one that causes the greatest positive spatial dependence between extreme losses but is followed by Brexit. Similar results on the US subprime crisis have been obtained in recent work by Chopra and Mehta [25], these authors showed that the sub-prime crisis was the most contagious for the Asian stock markets. In addition, previous works also showed the contagion of this crisis in different financial markets around the world, see [16,17].…”
Section: Discussionsupporting
confidence: 87%
“…More recently, various studies have analysed the impact of the COVID-19 pandemic on financial markets. For example, Chopra and Mehta [25] used a multivariate DCC-GARCH model of log-returns to compare the presence of contagion for the Asian stock markets during the four main financial crises: the Asian financial crisis, the US sub-prime crisis, the Eurozone debt crisis and the COVID-19 pandemic. The results showed that the US sub-prime crisis was the most contagious for the Asian stock markets, while the impact of the COVID-19 pandemic was the least contagious.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the changes from the 2007/2008 global financial crisis to the Covid-19 Global Pandemic, it is noted that much progress has been made in the discussion of what would be the appropriate levels of indebtedness and borrowing. Topics such as the economic impact of credit supply without prior analysis, bank failure, rising unemployment, GDP contraction, and inadequate resource allocation are among the consequences of excessive indebtedness (Chopra & Mehta, 2022). However, the current analysis for granting credit still seems to have not evolved enough, since it is based mainly on individual income and the individual's credit history, not being sufficiently considered the expenses that the applicant already has to maintain their survival (Ganbat et al, 2021).…”
Section: Final Considerationsmentioning
confidence: 99%
“…Several studies have explored this impact. Chopra and Mehta (2022) explore the contagious effects of the COVID-19 pandemic on the Asian stock markets. Ludvigson et al (2020) and Sharif et al (2020) analyze the possible impact of COVID-19 on the macroeconomy.…”
Section: Background and Literature Reviewmentioning
confidence: 99%